Development of new partial steam distribution method for providing partial operating modes of powerful steam turbines - Русанов, Андрей Викторович; Косьянова, Анна Игоревна; Косьянов, Дмитрий Юрьевич (Eastern-European Journal of Enterprise Technologies, 2015)
A new approach to the partial steam distribution - radial steam distribution was presented. On its basis, a prototype of the control compartment for steam turbine K-325-23, 5 without the surge chamber, designed to provide partial operating modes of the turbine was developed. A theoretical scheme of the control stage with radial steam admission to annular chambers was proposed. Flow visualization and integral characteristics of the developed flowing part were given, and analysis of features of the physical processes occurring in the radial steam admission was performed. It was found that using radial partial steam distribution provides the necessary parameters of the partial operating modes of the steam turbine. Effect of radial partiality on gas-dynamic efficiency parameters appears to a greater extent in the control stage and to a substantially lesser extent in the second and third stages.